Urania Titani, a Satire on Tycho Brahe’s Exile - Andersen, Peter (Sensus Historiae, 2024)
Urania Titani is a farewell poem written by Urania to her lover Titan, who has left her behind in search of gold abroad. It was found among Tycho Brahe’s papers after his death in Prague in 1601. Traditionally, Urania is identified with the astronomer’s younger sister, Titan with her fiancé, and Tycho is thought to have composed the poem on his sister’s behalf to lure her fiancé back to Denmark. According to a new reading, it is a satire composed by the astronomer’s enemy Jon Jacobsen Venusinus.